Case report: Naturally occurring neurogenic stunned myocardium in a dog secondary to status epilepticus - Dunham, Jacob; Horridge, Mallory; Lim, Ji-Hey; Lyons, Bridget M.; Wiggen, Kelly (Frontiers in Veterinary Science, 2024)
A 4-year-old male-neutered Boston Terrier was presented in status epilepticus. He was diagnosed with idiopathic epilepsy and hospitalized with supportive care. During hospitalization, the patient developed both supraventricular and ventricular arrhythmias as well as focal left ventricular dyskinesis. Cardiac troponin I was significantly increased, supportive of myocardial damage. Neurogenic stunned myocardium was suspected, and the patient was treated and responsive to esmolol. Follow-up echocardiography demonstrated resolution of the ventricular dyskinesia. This report describes the clinical presentation, diagnostic findings, treatment, management, and outcome of the first reported case of naturally occurring neurogenic stunned myocardium in a dog. Electrocardiogram monitoring, cardiac troponin I, and echocardiography should be considered in patients presenting with seizure activity, especially when exhibiting cluster seizures or in status epilepticus.